(3GdUGOM hGdHGZes - (3eMeO Hf eMeO Hf UGdM GdYHGSj, fXGe GdOjf CHh jYdj, GHf GdgHGQjI , J (B509 (3g` s
(3ChdgG (B:s
(3GdMeO ddg GdPj MHGfj HGdCUZQjf GdbdH hGddSGf s
(3BNQgG (B:s
(3Ef GdaNGQ hGdYdG EQKc ef Ohf GdedG Je GdcJGH fSNoG HMeO Gddg s
(3fSNI KGdKIs
(3hgj eUMMIs
(3Je JUMjMgG YGe (B878(3g`s
(3hHgG fXGe GdJYbjHIs
(3hHChdgG Jedc eDQN SfI (B1112(3g`s
(3JJab aj ChdgG hBNQgG eY GdfSNI GdKGfjI eY GNJdGa aj HYV GdCdaGX s
Keywords: (3GdCOHs